Role of Glucagon in The Metabolic Response: Review - Tona, Azwar Iwan; Syukri, Maimun (Journal of Society Medicine, 2023)
Historically, glucagon is the counter-regulatory hormone of insulin. Glucagon secretion is induced by fasting conditions or hypoglycaemia to increase glucose levels. Glucagon is the dominant product of alpha cells in the islet and was first identified in 1923 during an attempt to purify insulin, where it was identified as a contaminant hyperglycaemia factor. Further research determined that the hyperglycaemic action of glucagon is mediated by increased hepatic glycogenolysis and gluconeogenesis to increase endogenous glucose production. Insulin and glucagon as opposing hormones work together for glycaemic control. Diabetic hyperglycaemia is caused by increased impaired insulin action and inappropriately elevated glucagon levels. This review summarizes an important function of glucagon is its role as a regulator of glucose homeostasis. Increased plasma glucagon levels lead to increased hepatic glucose production. The balance between insulin and glucagon is responsible for maintaining euglycaemia conditions. In conditions of hypoglycaemia, increased glucagon secretion leads to increased hepatic glucose production through a number of cellular mechanisms including suppression of glycogenesis and glycolysis and stimulation of glycogenolysis and gluconeogenesis